Efficacy and safety of inhaled once-daily low-dose indacaterol acetate/mometasone furoate in patients with inadequately controlled asthma: Phase III randomised QUARTZ study findings. (January 2020) - Kornmann, Oliver; Mucsi, Janos; Kolosa, Nadezda; Bandelli, Lorraine; Sen, Biswajit; Satlin, Lisa C.; D'Andrea, Peter
Abstract: Background: Global initiative for asthma (GINA) 2019 recommends adding a long-acting β2 -agonist (LABA) to an inhaled corticosteroid (ICS) as a maintenance controller therapy in patients with inadequately controlled asthma. Indacaterol acetate (IND, a LABA) in combination with mometasone furoate (MF, an ICS) is under development for the treatment of these patients. Objective: This phase III QUARTZ was a multicentre, randomised, double-blind, double-dummy and parallel-group study to assess the efficacy and safety of low-dose IND/MF 150/80 μg once daily (o.d.) versus MF 200 μg o.d. in adult and adolescent patients with inadequately controlled asthma. Methods: Eligible patients (n = 802) were randomised (1:1) to receive either low-dose IND/MF 150/80 μg o.d. via Breezhaler® or MF 200 μg o.d. via Twisthaler® for 12 weeks. Primary endpoint was trough forced expiratory volume in 1 s (FEV1 ) and key secondary endpoint was Asthma Control Questionnaire (ACQ-7) treatment difference after 12-week treatment. Other secondary endpoints included ACQ-7 responder analysis, morning and evening peak expiratory flow, Asthma Quality of Life Questionnaire total score, rescue medication use, daily symptom score, nighttime awakenings and rate of exacerbations, evaluated over 12-week treatment. Safety was also assessed including serious asthma outcomes. Results: Low-dose IND/MF significantly improved trough FEV1 (least squares mean treatment difference [LSMTD]: 0.182 L; p < 0.001) and ACQ-7 (LSMTD: −0.218; p < 0.001) versus MF at Week 12. Improvements in all other secondary endpoints favoured low-dose IND/MF. Safety was comparable. Conclusion: These results support the use of low-dose IND/MF 150/80 μg o.d. as a potential therapy for adult and adolescent patients with inadequately controlled asthma. Highlights: What is already known about this topic? Many patients remain symptomatic despite receiving ICS monotherapy. The recent update in GINA 2019 recommends the addition of long-acting β2 -agonist (LABA) to ICS monotherapy as the preferred controller and maintenance therapy in patients with inadequately controlled asthma. What does this article add to our knowledge? To our knowledge, this is the first study to compare a low-dose ICS/LABA FDC o.d. to low-dose ICS monotherapy in adult and adolescent patients with inadequately controlled asthma. How does this study impact current management guidelines? Once-daily, low-dose IND/MF can be a potential option for treatment of adult and adolescent patients with asthma who remain inadequately controlled on ICS (with/without LABA). Data from this study add to the existing evidence supporting, the efficacy of ICS/LABA over ICS alone and the efficacy of a once-daily combination of low-dose IND/MF 150/80 μg o.d., in patients with inadequately controlled asthma.